Memories of Violence in Transit and Unsubmissive Subjectivities in Aida Gomes and Yara Monteiro - Rendeiro, Margarida (2024)
Besides pluralizing critical views of the colonial past and its effects in the present and breaking hegemonic silences, the literary works of Portuguese women writers of African descent introduce intersectional perspectives on the (post-) memories of the colonial past created in Atlantic transit, especially between Portugal and Angola. This article examines Os Pretos de Pousaflores (2011), by Aida Gomes, and Essa Dama Bate Bué! (2018), by Yara Monteiro as narratives that articulate gendered violence as a silenced continuum of intergenerational women’s stories that permeate colonialism, and Angolan liberation struggles to the present-day. Drawing on Lionnet’s (1999) and Kalisa’s (2009) studies on representations of stories of gender violence, it is argued that women are portrayed as non-submissive subjects whose agency contradicts patriarchal rhetoric. Storytelling is a healing mechanism for silenced violence. It is also argued that the female figure is a postcolonial metaphor that challenges patriarchal representations of motherhood that not even the rhetoric of Angolan liberation forces overcame.